Optofluidic ultrahigh-throughput detection of fluorescent drops1. Issue 6 (21st March 2015) - Kim, Minkyu; Pan, Ming; Gai, Ya; Pang, Shuo; Han, Chao; Yang, Changhuei; Tang, Sindy K. Y.
<x xml:space="preserve">Abstract</x> We describe a novel optofluidic device directly integrated with a two-dimensional CMOS sensor capable of counting fluorescent drops at a rate of 254 000 drops s−1.